Collaborative Governance Between Surabaya City and Blitar Regency in Regional Economic Development - Muhammad Hazel Rahman Saleh; Chika Dhesti Rahmadhani; M. Fadlan Dhafinsyah; Nova Eviolina (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2026)
This study aims to analyze the implementation of cooperation between the Surabaya City Government and the Blitar Regency Government in supporting regional economic development through a collaborative governance approach. The study employed a qualitative approach using a literature review method. Data were collected from scientific journals, books, government policies, official reports, and publications related to interregional cooperation. Data analysis applied the interactive model through data reduction, data presentation, and conclusion drawing, supported by open, axial, and selective coding techniques. The findings show that interregional collaboration has been relatively effective in strengthening food commodity distribution, developing digital-based MSMEs, and promoting cross-regional tourism. The collaboration contributed to increased distribution of agricultural and livestock products from Blitar Regency to Surabaya, including the supply of approximately 5 tons of eggs, expanded MSME market access through digital marketing, and the establishment of integrated tourism promotion. However, several challenges remain, including low digital literacy among MSME actors, limited supporting infrastructure, and disparities in regional economic capacity. This study contributes to strengthening collaborative governance studies as a strategy for regional economic connectivity based on food distribution, MSME development, and interregional tourism.